The distinctive morphology of caudal neurosecretory system and its impact on Pampus argenteus throughout the breeding season - Guo, Chunyang; Zhang, Xiaodong; Song, Huiyang; Wang, Xubo; Xu, Shanliang; Wang, Danli (Frontiers in Marine Science, 2024)
The caudal neurosecretory system (CNSS) of teleost is intricately linked to reproduction. This study sought to explore the association between the CNSS and the reproductive cycle of Pampus argenteus. Utilizing microscopy and transmission electron microscopy, we observed the morphological alterations within the CNSS. Furthermore, we quantified the levels of urotensin-I (U-I), urotensin-II (U-II), cortisol, and corticotropin-releasing hormone (CRH) throughout the reproductive process. Findings revealed that Dahlgren cells, distributed along the spinal cord adjacent to the terminal 6 vertebrae of the silver pomfret’s tail, were primarily concentrated within the final 3 vertebrae. The neurohypophysis was characterized by an elongated oval form when viewed laterally and an almost spherical configuration in ventral perspective. Post-breeding season, the average diameters of Type I and Type II Dahlgren cells decreased by 21.8% and 15.44%, respectively (P < 0.05), accompanied by a reduction in neurosecretory granules to merely 60% of their initial pre-reproductive state (P < 0.05). Variations in the serum and gonadal concentrations of U-I, U-II, cortisol, and CRH indicated a significant correlation with gonadal maturation. In summary, the CNSS plays a crucial role in gonadal development, directly or indirectly influencing and modulating the reproductive activities of P. argenteus.